Top cop jets out on world trip - Adlam, Nigel.; Smith, Camden.
tag=1 data=Top cop jets out on world trip tag=2 data=Adlam, Nigel%Smith, Camden tag=3 data=NT News tag=8 data=POLICE-NT tag=9 data=AROUND THE WORLD TRIP%JUNKETS TO CANADA%INUIT HOMELANDS tag=32 data=WHITE, PAUL%BURKE, DENIS%HATTON, STEVE%BRAHAM, LORAINELL, NEIL tag=34 data=PRSS tag=61 data=23 tag=62 data=Aug tag=63 data=2002